Analysis of Three Techniques in Constrcting OFET - Wu, Perry (Transactions on Computer Science and Intelligent Systems Research, 2024)
The Organic Field-Effect Transistor (OFET) boasts several salient features including flexibility, reduced power consumption, and enhanced biocompatibility, positioning it as a pivotal component in the advancement of flexible electronics, wearable technologies, and medical electronic devices. Despite its considerable attributes, the OFET’s widespread adoption is hindered by inherent limitations, notably its low carrier mobility. Consequently, there is a concerted effort within the research community to augment OFET performance. This manuscript delineates three predominant methodologies employed in the fabrication of the organic semiconductor layer integral to OFETs: spin-coating, dip-coating, and inkjet printing techniques. For each method, a comprehensive analysis of its underlying principles, procedural intricacies, and performance metrics—such as carrier mobility, cost-efficiency, crystal quality, and applicability scope—is presented. Additionally, empirical instances employing these techniques are meticulously examined to furnish a clearer comprehension of their practical implications. This paper contribution aims to equip future investigators with the knowledge to judiciously select appropriate techniques for their research endeavors, thereby facilitating the evolution of OFET technology.